PHYSIOTHERAPY TREATMENT FOR NEURODERMATITIS - Norqulova , Xadicha Yusuf qizi; Xakimov , Dilshod Rustamovich (Educational Research in Universal Sciences, 2024)
Neurodermatitis, also known as atopic dermatitis, is a chronic inflammatory skin condition that is often accompanied by itching, dryness and redness of the skin. This condition can significantly affect the patient's quality of life, causing discomfort and psychological distress. Although neurodermatitis has no specific cure, physical therapy techniques can be effective in managing symptoms and improving skin conditions. In recent years, physiotherapy treatment for neurodermatitis has become an increasingly popular and effective method of managing symptoms and improving patients' quality of life. In this article, we review the main physical therapy modalities used for neurodermatitis and discuss their efficacy based on existing research.